A composite hole transport layer and a preparation method of a perovskite solar cell

CN123022091APending Publication Date: 2026-10-30HANGZHOU MICROQUANTA SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510491366.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但实验发现,由于能级不匹配、氧化镍表面缺陷、润湿性、锚定基团的反应性不够等因素共同作用导致氧化镍表面羟基与SAM分子结合能力弱,键合不够牢固,无法在衬底上形成均匀分布,限制了大面积钙钛矿太阳能电池的进一步发展

Benefits of technology

1、提高界面结合力:本发明通过将氧化铝纳米颗粒(Al2O3NPs)和SAM自组装分子预结合,作为HTL,可以有效防止氧化镍(NiOx)和SAM自组装材料的直接接触,避免了由于化学性质差异导致的氧化镍(NiOx)与SAM自组装材料界面结合力不足的问题。这种物理、可见的涂覆过程,相较于现有的发生在界面的自组装化学键合过程,可以更好地控制和优化界面修饰效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022091A_ABST
    Figure CN123022091A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of perovskite solar cell preparation, and relates to a composite hole transport layer and a preparation method of a perovskite solar cell. The preparation method of the composite hole transport layer comprises the following steps: dispersing aluminum oxide nanoparticles in a solution of SAM self-assembled small molecules, and performing ultrasonic dispersion to form a uniform dispersion liquid of aluminum oxide and SAM; adding phenylsilane with a concentration of 0.001 mg / ml to 1 mg / ml into the dispersion liquid to obtain a precursor solution; coating the precursor solution on the surface of a hole transport layer which has been prepared in advance in air, and obtaining a hole interface layer after drying, wherein the hole transport layer and the hole interface layer constitute the required composite hole transport layer. The application improves the interface bonding force of the composite hole transport layer, optimizes the interface modification effect, improves the self-assembly coverage and uniformity of SAMs, improves the production efficiency, reduces the production cost, and improves the long-term stability and aging resistance of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite solar cell fabrication technology, and specifically relates to a composite hole transport layer and a method for fabricating perovskite solar cells. Background Technology

[0002] In recent years, perovskite solar cells have attracted widespread attention. Perovskite solar cells use organometal halides as the light-absorbing layer. Perovskite has an ABX3 type cubic octahedral structure. Thin-film solar cells made from this material are simple to manufacture, have low production costs, are stable, and have high conversion efficiency. Since 2009, the photoelectric conversion efficiency has increased from 3.8% to over 26.6%, which is comparable to commercial crystalline silicon solar cells in terms of efficiency and has a significant cost advantage.

[0003] In the past two years, inverted perovskite solar cells have developed rapidly, with a significant improvement in photoelectric conversion efficiency. Professor Xu Jixian's team at the University of Science and Technology of China set a certified world record of 26.7% for steady-state efficiency of perovskite cells, which was included in the authoritative international world record list, *Solar Cell Efficiency Tables*. This rapid development is mainly attributed to the rapid advancement of self-assembled molecular materials (SAMs). Most existing technologies involve re-fabricating SAM molecules on a nickel oxide hole transport layer. However, experiments have shown that factors such as energy level mismatch, nickel oxide surface defects, wettability, and insufficient reactivity of anchoring groups result in weak bonding between the hydroxyl groups on the nickel oxide surface and SAM molecules, leading to insufficiently strong bonds and an inability to form a uniform distribution on the substrate, thus limiting the further development of large-area perovskite solar cells. Furthermore, the phosphate groups in SAM molecules are easily oxidized, requiring coating under nitrogen atmosphere. Additionally, the energy levels of SAM molecules change due to various factors after aging, affecting the performance of perovskite solar cells. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a composite hole transport layer and a method for preparing perovskite solar cells. This method not only improves the interfacial bonding force between the hole transport layer and the hole interface layer and optimizes the interface modification effect, but also improves the coverage and uniformity of SAM self-assembly. Furthermore, it simplifies the process flow, improves production efficiency, reduces production costs, improves the performance of perovskite solar cells, and enhances the long-term stability and aging resistance of perovskite solar cells.

[0005] This invention is implemented by providing a composite hole transport layer, comprising the following steps: Step 1: Prepare a hole transport layer on the surface of a substrate containing a conductive layer; Step 2: Disperse alumina nanoparticles in a solution of SAM self-assembled small molecules and perform ultrasonic dispersion to form a uniform dispersion of alumina and SAM; add phenylsilane at a concentration of 0.001 mg / ml to 1 mg / ml to the dispersion to obtain a precursor solution. Step 3: In air, the precursor solution is coated onto the surface of the pre-prepared hole transport layer. After drying, a hole interface layer is obtained. The hole transport layer and the hole interface layer constitute the desired composite hole transport layer; wherein, The alumina nanoparticles have a particle size range of 5 nm to 50 nm and a mass fraction of 0.01% to 2% in the dispersion. The SAM self-assembled molecules are self-assembled molecules containing at least one phosphate group and have a concentration of 0.1 mg / ml to 2 mg / ml. The dispersion solvent is at least one solvent selected from DMF, ethanol, isopropanol, and tetrahydrofuran.

[0006] This invention is achieved by providing a method for fabricating a perovskite solar cell, comprising the following steps: Step 1: Clean and treat the substrate with the transparent conductive layer using ultraviolet ozone; Step 2: Using the method for preparing a composite hole transport layer as described above, prepare a composite hole transport layer on the surface of the transparent conductive layer. Step 3: Prepare a perovskite light-absorbing layer on the composite hole transport layer; Step 4: Prepare an electron transport layer on the perovskite light-absorbing layer; Step 5: Fabricate a back electrode on the electron transport layer to complete the fabrication of the perovskite solar cell; wherein, the perovskite light-absorbing layer is made of perovskite material with the molecular formula ABX3, wherein A is at least one monovalent cation from cesium, rubidium, amino, amidine, and base groups; B is at least one divalent metal cation from lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium; and X is at least one anion from iodine, bromine, chloride, astatine, thiocyanate, and acetate.

[0007] Compared with the prior art, the composite hole transport layer and the fabrication method of the perovskite solar cell of the present invention have the following characteristics: 1. Improved interfacial bonding: This invention pre-bonds alumina nanoparticles (Al2O3NPs) and SAM self-assembled molecules as HTL, which can effectively prevent nickel oxide (NiO) from oxidizing. x Direct contact between the material and the SAM self-assembled material avoids nickel oxide (NiO) oxidation caused by differences in chemical properties. x This addresses the issue of insufficient interfacial bonding between the coating and SAM self-assembled materials. Compared to existing self-assembly chemical bonding processes that occur at the interface, this physical, visible coating process allows for better control and optimization of the interface modification effect.

[0008] 2. Optimized Interface Modification Effect: This invention transforms the chemical bonding process of self-assembly into a physical, visible coating process, making the interface modification effect more controllable and optimized. By adjusting the ratio and proportion of alumina nanoparticles and SAM self-assembled molecules, the thickness and uniformity of the interface modification can be precisely controlled, thereby improving the performance of the HTL (hole transport layer).

[0009] 3. Improved SAM self-assembly coverage and uniformity: This invention transforms the SAM self-assembly process into a physical, visible coating process, effectively improving the coverage and uniformity of SAM self-assembled materials. Compared to traditional chemical reaction processes, physical coating processes are less affected by environmental factors, thus allowing for more stable control of the coverage and uniformity of SAM self-assembled materials, further enhancing HTL performance.

[0010] 4. Simplified process flow: This invention simplifies the existing multilayer structure process flow by combining alumina nanoparticles and SAM self-assembled molecules as HTL, thereby improving production efficiency and reducing production costs.

[0011] 5. The addition of phenylsilane can effectively prevent the oxidation of phosphate groups in SAM molecules, enabling large-area coating in air, and solving the oxidation problem of SAM molecules during aging, thereby improving the stability of perovskite solar cells. Attached Figure Description

[0012] Figure 1 This is a comparison chart of the IV performance of the perovskite solar cell prepared in Example 1 of the present invention and the perovskite solar cell prepared in the comparative example. Figure 2 This is a comparison chart of the average UV aging degradation rate of the perovskite solar cell prepared in Example 1 of the present invention and the perovskite solar cell prepared in the comparative example. Detailed Implementation

[0013] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.

[0014] A preferred embodiment of the method for preparing the composite hole transport layer of the present invention includes the following steps: Step 1: Prepare a hole transport layer on the surface of a substrate containing a conductive layer.

[0015] Step 2: Disperse alumina nanoparticles in a solution of SAM self-assembled small molecules and perform ultrasonic dispersion to form a uniform dispersion of alumina and SAM; add phenylsilane at a concentration of 0.001 mg / ml to 1 mg / ml to the dispersion to obtain a precursor solution.

[0016] Step 3: In air, the precursor solution is coated onto the surface of the pre-prepared hole transport layer. After drying, a hole interface layer is obtained. The hole transport layer and the hole interface layer together form the desired composite hole transport layer.

[0017] The alumina nanoparticles have a particle size range of 5nm to 50nm and a mass fraction of 0.01% to 2% in the dispersion. The SAM self-assembled molecules are self-assembled molecules containing at least one phosphate group and have a concentration of 0.1mg / ml to 2mg / ml. The dispersion solvent is at least one solvent selected from DMF, ethanol, isopropanol, and tetrahydrofuran.

[0018] The thickness of the hole transport layer is 5nm to 30nm. The thickness of the hole interface layer is 5nm to 50nm.

[0019] This invention also discloses a method for preparing a perovskite solar cell, comprising the following steps: Step 1: Clean and treat the substrate with the transparent conductive layer with ultraviolet ozone.

[0020] Step 2: Using the method described above for preparing a composite hole transport layer, prepare a composite hole transport layer on the surface of the transparent conductive layer.

[0021] Step 3: Prepare a perovskite light-absorbing layer on the composite hole transport layer.

[0022] Step 4: Prepare an electron transport layer on the perovskite light-absorbing layer.

[0023] Step 5: Fabricate the back electrode on the electron transport layer to complete the fabrication of the perovskite solar cell.

[0024] The perovskite light-absorbing layer is prepared by a perovskite material with the molecular formula ABX3, wherein A is at least one monovalent cation from cesium, rubidium, amino, amidine, and base groups; B is at least one divalent metal cation from lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium; and X is at least one anion from iodine, bromine, chloride, astatine, thiocyanate, and acetate.

[0025] The preparation method of the perovskite solar cell of the present invention is further illustrated below through specific embodiments.

[0026] Example 1

[0027] The first embodiment of the method for fabricating perovskite solar cells of the present invention includes the following steps: Step 11: Clean the ITO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes.

[0028] Step 12: Preparation of nickel oxide hole transport layer: Spin-coat a 0.15M nickel nitrate hexahydrate ethanol solution onto an ITO transparent conductive glass substrate at 4000 rpm for 30 s, and then burn at 300℃ for 30 min to obtain the nickel oxide hole transport layer.

[0029] Step 13: Preparation of alumina and SAM dispersion: Dissolve 0.2 mg of 2PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles with a mass fraction of 0.1%, and sonicate for 30 min to disperse evenly; add 0.02 mg / ml phenylsilane to the dispersion and sonicate for 30 min to further disperse, to obtain the precursor solution.

[0030] Step 14: The prepared precursor solution is used to perform slit coating on the surface of the hole transport layer in air, and after drying, a hole interface layer with a thickness of 30 nm is obtained.

[0031] Step 15: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with PCBM as an electron transport layer and BCP as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

[0032] Example 2

[0033] A second embodiment of the method for preparing perovskite solar cells of the present invention includes the following steps: Step 21: Clean the FTO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes.

[0034] Step 22: Prepare NiO on an FTO transparent conductive glass substrate using magnetron sputtering. x Hole transport layer.

[0035] Step 23: Preparation of alumina and SAM dispersion: Dissolve 0.2 mg of MeO-PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles with a mass fraction of 0.05%, and sonicate for 30 min to disperse evenly; add 0.02 mg / ml phenylsilane to the dispersion, and sonicate for 30 min to further disperse, to obtain the precursor solution.

[0036] Step 24: Using the prepared precursor solution in air, slit coating is performed on the surface of the hole transport layer to prepare a hole interface layer with a thickness of 10 nm.

[0037] Step 25: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with C60 as an electron transport layer and zirconium acetylacetonate as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

[0038] Example 3

[0039] A third embodiment of the method for fabricating perovskite solar cells of the present invention includes the following steps: Step 31: Clean the ITO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes.

[0040] Step 32: Preparation of nickel oxide hole transport layer: Spin-coat a 0.15M nickel acetylacetonate ethanol solution onto an ITO transparent conductive glass substrate at 4000 rpm for 30 s, and then burn at 350℃ for 30 min to obtain the nickel oxide hole transport layer.

[0041] Step 33: Preparation of alumina and SAM dispersion: Dissolve 0.1 mg of 2PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles with a mass fraction of 0.01%, and sonicate for 30 min to disperse evenly; add 0.001 mg / ml phenylsilane to the dispersion and sonicate for 30 min to further disperse, to obtain the precursor solution.

[0042] Step 34: The prepared precursor solution is used to perform slit coating on the surface of the hole transport layer in air, and after drying, a hole interface layer with a thickness of 5 nm is obtained.

[0043] Step 35: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with PCBM as an electron transport layer and BCP as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

[0044] Example 4

[0045] A fourth embodiment of the method for fabricating perovskite solar cells of the present invention includes the following steps: Step 41: Clean the FTO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes.

[0046] Step 42: Prepare NiO on an FTO transparent conductive glass substrate using magnetron sputtering. x Hole transport layer.

[0047] Step 43: Preparation of alumina and SAM dispersion: Dissolve 2 mg of MeO-PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles (2% by mass), and sonicate for 30 min to disperse evenly; add 1 mg / ml phenylsilane to the dispersion and sonicate for 30 min to further disperse, to obtain the precursor solution.

[0048] Step 44: Using the prepared precursor solution in air, slit coating is performed on the surface of the hole transport layer to prepare a hole interface layer with a thickness of 30 nm.

[0049] Step 45: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with C60 as an electron transport layer and zirconium acetylacetonate as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

[0050] Please refer to Figure 1 The figure shows a comparison of the IV performance of the perovskite solar cell prepared in Example 1 of this invention and the perovskite solar cell prepared in the comparative example. From... Figure 1 It can be seen that the voltage and fill factor are significantly improved, indicating that the interface is significantly optimized and the coverage of the composite hole transport layer is significantly improved compared with the single-layer SAM.

[0051] The perovskite solar cell prepared in the comparative example differs from the perovskite solar cell prepared in Example 1 in that an interface layer made of SAM self-assembled small molecule material (2PACz) is prepared on the surface of the hole transport layer, while the other steps and conditions are the same as in Example 1.

[0052] Please refer to Figure 2 The figure shows a comparison of the average UV aging degradation rate of the perovskite solar cell prepared in Example 1 of this invention and the perovskite solar cell prepared in the comparative example. From... Figure 2 As can be seen, in the perovskite solar cell of Example 1, the coating of alumina nanoparticles and the addition of phenylsilane in the composite hole transport layer effectively prevent oxidation and direct contact with the nickel oxide substrate, which significantly improves the UV stability of the perovskite solar cell. After 100 kWh of UV aging, the degradation is less than 5%, and after 150 kWh of aging, the degradation is less than 10%, which is a significant improvement in stability compared with the perovskite solar cell with direct contact in the comparative example.

[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a composite hole transport layer, characterized in that, Includes the following steps: Step 1: Prepare a hole transport layer on the surface of a substrate containing a conductive layer; Step 2: Disperse alumina nanoparticles in a solution of SAM self-assembled small molecules and perform ultrasonic dispersion to form a uniform dispersion of alumina and SAM; add phenylsilane at a concentration of 0.001 mg / ml to 1 mg / ml to the dispersion to obtain a precursor solution. Step 3: In air, the precursor solution is coated onto the surface of the pre-prepared hole transport layer. After drying, a hole interface layer is obtained. The hole transport layer and the hole interface layer constitute the desired composite hole transport layer; wherein, The alumina nanoparticles have a particle size range of 5 nm to 50 nm and a mass fraction of 0.01% to 2% in the dispersion. The SAM self-assembled molecules are self-assembled molecules containing at least one phosphate group and have a concentration of 0.1 mg / ml to 2 mg / ml. The dispersion solvent is at least one solvent selected from DMF, ethanol, isopropanol, and tetrahydrofuran.

2. The method for preparing the composite hole transport layer as described in claim 1, characterized in that, The thickness of the hole transport layer is 5nm~30nm.

3. The method for preparing the composite hole transport layer as described in claim 1, characterized in that, The thickness of the hole interface layer is 5nm~50nm.

4. A method for fabricating a perovskite solar cell, characterized in that, Includes the following steps: Step 1: Clean and treat the substrate with the transparent conductive layer using ultraviolet ozone; Step 2: Using the method for preparing a composite hole transport layer as described in any one of claims 1 to 3, prepare a composite hole transport layer on the surface of a transparent conductive layer; Step 3: Prepare a perovskite light-absorbing layer on the composite hole transport layer; Step 4: Prepare an electron transport layer on the perovskite light-absorbing layer; Step 5: Fabricate a back electrode on the electron transport layer to complete the fabrication of the perovskite solar cell; wherein, the perovskite light-absorbing layer is made of perovskite material with the molecular formula ABX3, wherein A is at least one monovalent cation from cesium, rubidium, amino, amidine, and base groups; B is at least one divalent metal cation from lead, tin, tungsten, copper, zinc, gallium, germanium, arsenic, selenium, rhodium, palladium, silver, cadmium, indium, antimony, osmium, iridium, platinum, gold, mercury, thallium, bismuth, and polonium; and X is at least one anion from iodine, bromine, chloride, astatine, thiocyanate, and acetate.

5. The method for preparing a perovskite solar cell as described in claim 4, characterized in that, Includes the following steps: Step 11: Clean the ITO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes. Step 12: Preparation of nickel oxide hole transport layer: Spin-coat a 0.15M nickel nitrate hexahydrate ethanol solution onto an ITO transparent conductive glass substrate at 4000 rpm for 30 s, and then burn at 300℃ for 30 min to prepare the nickel oxide hole transport layer. Step 13: Preparation of alumina and SAM dispersion: Dissolve 0.2 mg of 2PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles (mass fraction 0.1%), sonicate for 30 min to disperse evenly; add 0.02 mg / ml phenylsilane to the dispersion, sonicate for 30 min to further disperse, and obtain the precursor solution; Step 14: The prepared precursor solution is used to perform slit coating on the surface of the hole transport layer in air, and after drying, a hole interface layer with a thickness of 30 nm is obtained. Step 15: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with PCBM as an electron transport layer and BCP as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

6. The method for preparing a perovskite solar cell as described in claim 4, characterized in that, Includes the following steps: Step 21: Clean the FTO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes. Step 22: Prepare NiO on an FTO transparent conductive glass substrate using magnetron sputtering. x Hole transport layer; Step 23: Preparation of alumina and SAM dispersion: Dissolve 0.2 mg of MeO-PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles (mass fraction 0.05%), sonicate for 30 min, and disperse evenly; add 0.02 mg / ml phenylsilane to the dispersion, sonicate for 30 min, and further disperse to obtain precursor solution; Step 24: Use the prepared precursor solution in air to perform slit coating on the surface of the hole transport layer to prepare a hole interface layer with a thickness of 10 nm. Step 25: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with C60 as an electron transport layer and zirconium acetylacetonate as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

7. The method for preparing a perovskite solar cell as described in claim 4, characterized in that, Includes the following steps: Step 31: Clean the ITO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes. Step 32: Preparation of nickel oxide hole transport layer: Spin-coat a 0.15M nickel acetylacetonate ethanol solution onto an ITO transparent conductive glass substrate at 4000 rpm for 30 s, and then burn at 350℃ for 30 min to obtain a nickel oxide hole transport layer. Step 33: Preparation of alumina and SAM dispersion: Dissolve 0.1 mg of 2PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles (mass fraction 0.01%), sonicate for 30 min, and disperse evenly; add 0.001 mg / ml phenylsilane to the dispersion, sonicate for 30 min, and further disperse to obtain the precursor solution; Step 34: The prepared precursor solution is used to perform slit coating on the surface of the hole transport layer in air, and after drying, a hole interface layer with a thickness of 5 nm is obtained. Step 35: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with PCBM as an electron transport layer and BCP as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.

8. The method for preparing a perovskite solar cell as described in claim 4, characterized in that, Includes the following steps: Step 41: Clean the FTO transparent conductive glass substrate sequentially with detergent, deionized water, acetone and isopropanol, and ultrasonically clean each for 30 minutes. Then dry it with N2 and treat it with UV O-zone for 10 minutes. Step 42: Prepare NiO on an FTO transparent conductive glass substrate using magnetron sputtering. x Hole transport layer; Step 43: Preparation of alumina and SAM dispersion: Dissolve 2 mg of MeO-PACz self-assembled molecules in 1 ml of ethanol, then add alumina nanoparticles (2% by mass), sonicate for 30 min to disperse evenly; add 1 mg / ml phenylsilane to the dispersion, sonicate for 30 min to further disperse, and obtain the precursor solution. Step 44: Using the prepared precursor solution in air, slit coating is performed on the surface of the hole transport layer to prepare a hole interface layer with a thickness of 30 nm. Step 45: Prepare a perovskite light-absorbing layer on the composite hole transport layer using a one-step solution method. Coat the perovskite light-absorbing layer with C60 as an electron transport layer and zirconium acetylacetonate as a blocking layer. Prepare a metal Ag back electrode on the blocking layer to complete the fabrication of the perovskite solar cell.